Left Carotid-to-Subclavian Artery Bypass Grafting for Recurrent Angina Caused by Coronary-Subclavian Steal Syndrome - Kim, Min-Seok (Korean Society for Thoracic and Cardiovascular Surgery, 2013)
A 60-year-old man visited the outpatient clinic due to one month of recurrent exertional chest pain. Eleven years earlier he had undergone off-pump coronary artery bypass grafting using bilateral internal thoracic artery (ITA) Y-composite grafts based on the left ITA. Preoperative coronary angiography showed patent distal graft anastomoses and visualized the left ITA retrogradely. The arch aortography revealed near-total occlusion of the left subclavian artery at the level of the ostium. The patient underwent left carotid-to-subclavian artery bypass grafting using a 6 mm vascular conduit. Postoperative computed tomographic angiography revealed a patent bypass conduit between the left common carotid artery and left subclavian artery. The patient was discharged on postoperative day 4 with no symptoms or signs of myocardial ischemia.